PENGARUH CITRA DESTINASI, PROMOSI, KUALITAS PELAYANAN TERHADAP KEPUASAN PENGUNJUNG DIRA SWIMMING POOL AMBULU - Sari, Maheni Ika; Winahyu, Pawestri; Ma’nunah, Zauharotul (Growth, 2022)
Study aims to determine and analyze the effect of destination image, promotion, service quality on visitor satisfaction at Dira Swimming Pool Ambulu. The primary data sources used in this study were respondents' answers through questionnaire items. The population of this study were all visitors to the Ambulu Dira Swimming Pool whose exact number could not be counted. Thus the number of samples in this study amounted to 80 respondents. The analytical tool used in this research is multiple linear regression analysis. Multiple regression test results show that the image of the destination has a positive effect on visitor satisfaction. This proves that a good destination image will increase visitor satisfaction at Dira Swimming Pool Ambulu. Promotion has a positive effect on visitor satisfaction. This proves that an attractive promotion will increase visitor satisfaction of Dira Swimming Pool Ambulu. Service quality has a positive effect on visitor satisfaction. This proves that good service quality will increase visitor satisfaction of Dira Swimming Pool Ambulu.